Installasi Base Transceiver Station (BTS) untuk Jaringan Node B pada Operator Hutchison 3 Indonesia (H3I) - Uzma Septima -; Lince Markis - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2015)
Base Transceiver Station is a device used to connect mobile-phone or smartphone in order to make long-distance communication, although in doing the movement or in transit from one place to another. Installation Base Transceiver Station for Network Node B At the operator Hutchison 3 Indonesia is done to make the operator Hutchison 3 Indonesia signal received by the phone for the better and not dashed when the user performs long-distance communication links with conditions in performing the movement or in the course of one place to another. Methods beginning the process of physical installation of Base Transceiver Station for Node B network in the operator Hutchison 3 Indonesia and order all the Base Transceiver Station can live well after the battery is connected to a rectifier and the required accuracy when performing the installation Base Transceiver Station. Furthermore, the integration process or Commissioning of the Base Transceiver Station for Node B network operator Hutchison 3 Indonesia on this in order to actively and After Commissioning obtained Receive Signal Level sectoral antennas of -59 dBm which can emit a signal as far as 7 km to 8 km , after the new process or Pointing connection between this new Base Transceiver Station Base Transceiver Station with preexisting and Pointing between Siak new Base Transceiver Station Base Transceiver Station Perawang with Perawang Students who have a distance of 5 km Receive Signal level of -32.4 dBm made in accordance with a budget link provided operator Hutchison 3 Indonesia is -30 dBm to -40 dBm.